Water quality and Sanitation status: A study on Char land of Bhuapur upazila under Tangail district (Journal of the Bangladesh Agricultural University, 2014)
The study was aimed to review the damage of sanitation facilities; since Char lands dwellers faces manifold challenges concerning sanitation, hygiene and water during flood. It also explored the possibilities of overcoming the negative impacts of floods on sources of safe drinking water and sanitation. The study result shows that, about 54% of the overall latrines were included ring slab with water seal, pit latrine, bush or hanging toilet of the flood affected people during the flood. Around 19% of the respondents use to do toilet in the open area during flood. Different NGOs e.g. Jamuna Char Development Project (JCDP), Bangladesh Rural Advancement Committee (BRAC), CARE and Red Crescent Society of Bangladesh works for rehabilitation of the flood affected people and give early warning on the flood. Depending on location and sanitation conditions, drinking water sources may be contaminated by flood water during flood and many waterborne diseases can spread out like Cholera, Dysentery, Diarrhoea, diseases of the skin, Typhoid etc. meantime. The conducted survey also reports that, drinking water and sanitation condition is not dependable (on the commentary of 64.8% of the responders). Therefore, the flood affected people of Bhuapur are usually underprivileged from appropriate sanitation facility on flood. They somehow conform themselves while a chain of problems strikes hardly during flood. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19895 J. Bangladesh Agril. Univ. 11(2): 209-214, 2013